Tawid-Gutom linkage-generative trans-institutional twin facilities as an urban connector between Quezon City and San Mateo - Bautista, Maria Daniella Adel B.; Gines, Leonido Jr. M. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
The ambiguity of the regional borders exhibits the disconnect between neighboring cities or
municipalities and their local government units (LGUs), only attempting to be defined by a
welcome arch. The Department of Agriculture had initiated a trans-institutional relationship
in addressing a national problem: CALABARZON provinces will provide fresh produce,
livestock, and fishery products to Metro Manila and to jump-start this project, the first site of
the “Food Basket” will be in San Mateo. Urban connectors are often imagined only as
bridges or road networks, but these can also be infrastructures on zonal boundaries that may
serve the localities it belongs to. The research will bring about more creative and more
deliberate structures co-owned by two localities–providing reciprocity between LGUs,
specifically in the context of food insecurity. This indicates the study of existing institutional
and industrial programs and their actualization. In doing so, institutional gaps that affect the
food value chain from production to consumption are revealed. The architectural design
proposal will bridge the fragmented relationship between the producer and the consumer
through a linkage-generative approach. The study aims to be a precedent in intermetropolitan
connections and define ambiguous boundaries. In this sense, linkage-generative architecture
describes a design that enables two or more stakeholders to create a connection between the
two of them. The resulting design output is a food innovation marketplace that aims to be the
go-to hub of those interested in product fortification. Still, day-to-day activities include
product development for Quezon City and San Mateo residents. The end-products of
Tawid-Gutom are fortified food items that are nutritious and just as affordable and accessible
as the cultural concept of pantawid-gutom food items.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Food supply -- Quezon City; Food supply -- San Mateo; Trans-institutional.